Combination of mentor-based and resident-based learning may benefit to improving the ability of clinical practice in resident training - Min Li; Tao Liu; Yiqiong Wen; Min Zhang; Wenye Zhu; Xuming Wang; Yunjiao Hou; Lin Li; Anju Zu; Shibo Sun (BMC Medical Education)
Abstract Background Mentor-based learning (MBL) is common teaching method in medical resident training and presents many shortcomings such as few practice opportunities and lack of efficiency. This study proposed the combination of mentor-based and resident-based learning (CMRL) and explored the role of CMRL in improving the effect of medical resident training. Methods Seventy-two residents who participated in standardized resident training (SRT) were recruited and randomly divided into the CMRL and MBL groups. The CMRL group adopted CMRL and MBL group adopted MBL for daily medical teaching for four weeks. The primary outcome measure was the difference in trainee's scores of comprehensive analysis ability between CMRL group and MBL group after teaching. The secondary outcome measures were the differences in trainee's scores of diagnosis ability, prescribing medical orders ability, and incorrect operations, as well as the differences in questionnaire scores of the trainee's communication skills and patient care between CMRL group and MBL group after teaching. Results The ability scores of CMRL group after teaching were higher than those before teaching (ability of diagnosis, 78.75 ± 17.83% vs. 67.08 ± 24.10%, p < 0.05; ability of comprehensive analysis 88.27 ± 10.95% vs. 69.56 ± 13.11%, p < 0.05; ability of prescribing medical orders, 90.03 ± 9.63% vs. 78.31 ± 10.28%, p < 0.05; respectively). In addition, scores of CMRL group in patient's evaluation on trainees after teaching were higher than that before teaching (communication skills 7.78 ± 1.02 scores vs. 6.22 ± 1.62 scores, p < 0.05; patient care 8.69 ± 0.92 scores vs. 6.92 ± 1.65 scores, p < 0.05; respectively). Meanwhile, the scores of CMRL group in ability of comprehensive analysis or prescribing medical orders after teaching were higher than those of MBL group. Moreover, scores of the trainee's communication skills and patient care in CMRL group were higher than those in MBL group after teaching. Conclusion CMRL is beneficial to improving residents' ability of comprehensive analysis and prescribing medical orders as well as residents' ability of communication skills and patient care in SRT. CMRL may be beneficial to improving the ability of clinical practice.